2011
DOI: 10.1212/wnl.0b013e31823d76aa
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cramp in pediatric Charcot-Marie-Tooth disease type 1A

Abstract: Objectives: To identify correlates of calf cramp in children with Charcot-Marie-Tooth disease type 1A (CMT1A).Methods: Throughout Australia, 81 children aged 2-16 years with CMT1A were recruited. Measures of strength, ankle range, foot posture, balance, agility, endurance, gait, and neurophysiology were collected. Post hoc logistic regression analyses were performed to identify independent predictors of calf cramp.Results: Of the 81 children, 26 (32%) reported calf cramp, and 1 child each reported toe, quadric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The search yielded an initial 454 articles (Fig. ), with a final yield of 10 eligible articles (Chan et al, ; Newman et al, ; Burns et al, ; ; ; Rose et al, ; Blyton et al, ; Ferrarin et al, ; ; Ounpuu et al, ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded an initial 454 articles (Fig. ), with a final yield of 10 eligible articles (Chan et al, ; Newman et al, ; Burns et al, ; ; ; Rose et al, ; Blyton et al, ; Ferrarin et al, ; ; Ounpuu et al, ) .…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary review of the 10 articles identified studies and samples that were described in more than one article, with data from seven independent studies identified. Notably, two articles appeared to describe gait of one sample (Ferrarin et al, ; ) and another three described a sample from a clinical trial of ascorbic acid (Burns et al, ; ; Blyton et al, ) (Correspondence with the lead author confirmed that two articles, Blyton et al ( ) and Burns et al ( ) , were post hoc analyses of baseline data from the Ascorbic acid study, Burns et al ( ) .). Table lists study characteristics of included articles.…”
Section: Resultsmentioning
confidence: 99%
“…Tremor in neuropathies has been described as disabling but no formal study of this has been undertaken,7 except in paediatric Charcot–Marie–Tooth disease where it has been shown to be one of the strongest independent determinants of reduced quality of life12; successful treatment in this context would likely have a substantial effect on quality of life. Tremor in this population also predicts other disabling symptoms 13. Currently, there is no consensus on the best way to treat neuropathic tremor, or why only some patients seem to be at risk of developing it.…”
Section: Introductionmentioning
confidence: 96%
“…Aerobic exercise produced only a modest impact on functional independence, although it did have a significant positive effect on mood state [49]. Muscle cramping and pain are common complaints among persons with CMT, and these symptoms may be exacerbated by exercise [57,58]. This outcome can be addressed by performing appropriate warm-up and cooldown sessions, along with ensuring adequate hydration.…”
Section: Weakness and Fatiguementioning
confidence: 99%